'Let's get wasted!' : a discourse analysis of teenagers' talk about binge drinking : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Science in Psychology (Health Endorsement) at Massey University, Manawatu campus, New Zealand - Chainey, Timothy Aarron (Massey University, 2011)
Teenage binge-drinking in New Zealand is a significant health issue that is on the rise. Understanding why teenagers drink in this manner - and whether they perceive their behaviours negatively - is essential to inform practice and policy aimed at reversing undesirable trends. This study used a social constructionist framework to explore how teenagers talked about binge drinking. It aimed to understand why they binge drink by examining the discourses they draw on to construct their behaviour and the subject positions offered by the discourses. Four semi-structured peer group interviews were conducted with 20 teenagers from Palmerston North, aged 16-18 years and with experience of drunkenness and binge drinking. A Foucauldian discourse analysis was conducted on the transcribed data. Participants talked about binge drinking in terms of ‘getting wasted’. A ‘social life’ discourse was used to construct this as ‘fun’ and something all teenagers do – alcohol is an integral part of their social lives. Participants also drew on an ‘alcohol is bad’ discourse, in which they acknowledged the risks and consequences of alcohol use. However, this discourse was actively resisted, which worked to justify their drinking and ensure they were not positioned negatively. How participants talked about getting wasted was also ‘gendered’. Binge drinking was constructed as a masculine activity, with males positioned as drinking to ‘get wasted’ and engage in risky behaviours. Female participants were positioned as drinking more for social reasons, but also with the intention of getting drunk. Alcohol-related sexual experiences provided subject positions when talking about ‘getting wasted’. Both genders were positioned as ‘getting wasted’ to have sex, with males constructed as ‘sex-obsessed animals’, and females as not wanting to admit it. These discourses together constructed ‘getting wasted’ as something positive and teenage-like, and position teenagers as engaging in behaviour that is not harmful or problematic. The findings from this study have implications for reducing this harmful drinking culture, and making drinking safer for teenagers in Palmerston North and New Zealand.
Keywords: Binge drinking; Teenage drinking; Alcohol use; Teenage attitudes; New Zealand drinking culture; Teenage behaviour